2023
DOI: 10.3390/su15032692
|View full text |Cite
|
Sign up to set email alerts
|

Can Green Financial Reform Policies Promote Enterprise Development? Empirical Evidence from China

Abstract: Green finance is considered a viable way to promote sustainable economic development and can effectively enhance enterprise development by alleviating financing constraints and eliminating liquidity risk. The Chinese government has formulated many policies to promote sustainable and enterprise development, including the green financial reform policy, but the implementation of the green financial reform policy is still unclear. In this context, this study employs the difference in difference (DID) method to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Many studies have investigated the importance of the PZGFRI in improving environmental protection and decreasing air pollution, however, empirical evidence on the impact of the PZGFRI on the ECS in China remains scarce. Many previous studies have corroborated the relationships between the PZFGRI and the environmental effect (Huang and Zhang, 2021), energy consumption intensity (Su et al, 2022), enterprise development (Yu et al, 2023), green innovation effect (Liu and Wang, 2023;Tang et al, 2023), air pollution and urban green development . According to the above-mentioned literature, few studies have focused on the impact of the PZGFRI on the ECS.…”
Section: Introductionmentioning
confidence: 74%
“…Many studies have investigated the importance of the PZGFRI in improving environmental protection and decreasing air pollution, however, empirical evidence on the impact of the PZGFRI on the ECS in China remains scarce. Many previous studies have corroborated the relationships between the PZFGRI and the environmental effect (Huang and Zhang, 2021), energy consumption intensity (Su et al, 2022), enterprise development (Yu et al, 2023), green innovation effect (Liu and Wang, 2023;Tang et al, 2023), air pollution and urban green development . According to the above-mentioned literature, few studies have focused on the impact of the PZGFRI on the ECS.…”
Section: Introductionmentioning
confidence: 74%
“…Many authors have conducted surveys on China's GFRI policy and its impact on innovations. The GFRI policy program supports green innovation in large, polluting companies and urban green development by enhancing total factor productivity in pilot cities, emphasizing the importance of debt finance in corporate green innovation [40,82,148,150,153,158]. A different study by Wang et al in 2022 [127] discovered that while the GFRP generally plays a positive role in fostering green technology innovation capabilities, the extent to which it has an impact varies depending on the region's resources, environment, and level of development, with middle-and high-income areas seeing a more noticeable impact.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars support Porter hypothesis (Porter and Van der Linde, 1995), which asserts that suitable environmental regulations can motivate enterprises to engage in innovation activities that enhance production efficiency as well as competitiveness [ 18 ], including Jaffe and Palmer (1997) [ 20 ], Ramanathan et al (2017) [ 21 ], Xue et al (2023) [ 5 ], Wang (2023) [ 22 ], Yu et al (2023) [ 23 ], Yan et al (2022) [ 14 ], Zhang et al (2021) [ 24 ], Zhang (2023b) [ 25 ], Xu et al (2023) [ 3 ], Li et al (2022b) [ 26 ], Chi and Yang (2023) [ 27 ], He et al (2024) [ 28 ], Zhang and He (2024) [ 29 ] and Wang et al (2023) [ 30 ]. For instance, Jaffe and Palmer (1997) found environmental compliance expenditure to be positively related to enterprises’ R&D spending [ 20 ].…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Yan et al (2022) noted that green financial reform significantly reduces enterprises' agency costs as well as increases the scale of R&D investment, boosting investment efficiency [14]. Furthermore, green financial pilot policies can also significantly improve enterprises' financing scale, and boost sustainable development capacity (Xu et al, 2023;Yu et al, 2023;Zhang, 2023b) [3,23,25]. Li et al (2022b) demonstrated that green finance reduces the enterprise debt cost by improving the social responsibility of enterprises [26].…”
Section: Literature Reviewmentioning
confidence: 99%